A scalable double-barcode sequencing platform for characterization of dynamic protein-protein interactions - Ulrich Schlecht (Nature Portfolio, 2017)
Protein-protein interactions (PPIs) play a major role in defining biological functions. Here, the authors present PPiSeq, a method to quantitatively score dynamic PPIs in yeast combining fragment complementation assays, genomic double-barcoding, and an analytical framework to precisely call fitness from barcode lineage trajectories.